2020
DOI: 10.1186/s12905-020-00904-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the quality of family planning counselling as part of routine antenatal care and its effect on intended postpartum contraceptive method choice among women in Nepal

Abstract: Background: Though modern contraceptive use among married women in Nepal has increased from 26% in 1996 to 43% in 2016, it remains low among postpartum women. Integration of counselling on family planning (FP) at the time of antenatal care (ANC) and delivery has the potential to increase post-partum contraceptive use. This study investigates the quality of FP counselling services provided during ANC visits and women's perceptions of its effectiveness in assisting them to make a post-partum family planning (PPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…These findings imply that 60% of the women missed FP counselling when they visited the facility for any health reason; while 31.2% and 26.4% missed FP counselling at ANC and post-natal care (PNC) visits respectively. Similarly findings have been reported elsewhere [8,14,16,18,24]. Kanyangara et al reported a 6% missed opportunity of FP counselling in sub-Saharan country sites.…”
Section: Plos Onesupporting
confidence: 79%
“…These findings imply that 60% of the women missed FP counselling when they visited the facility for any health reason; while 31.2% and 26.4% missed FP counselling at ANC and post-natal care (PNC) visits respectively. Similarly findings have been reported elsewhere [8,14,16,18,24]. Kanyangara et al reported a 6% missed opportunity of FP counselling in sub-Saharan country sites.…”
Section: Plos Onesupporting
confidence: 79%
“…Therefore, women with higher education levels can increase women's knowledge about contraceptive use. In addition, these findings indicate that education has a positive impact on women's willingness to use the IUD after delivery (Puri, Moroni, et al, 2020).…”
Section: Overview Of the Third Trimester Pregnant Women's Attitudes A...mentioning
confidence: 76%
“…These settings provide safe and acceptable opportunities to improve IPP LARC access and prevent RRP. 75,76 Community-based programs may address knowledge gaps through provision of comprehensive information about LARC and contraceptive decision support, providing opportunities to obtain advice from trusted peer educators 69 and health professionals in tandem. However, introducing male partners in contraceptive choices requires careful navigation and further research, with a recent study cautioning the promotion of increased engagement of men in family-planning decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing autonomous contraception decision‐making in developing contexts may be achieved through the availability of dedicated family planning counselors in both hospital and community settings to enhance postpartum and post‐abortion care. These settings provide safe and acceptable opportunities to improve IPP LARC access and prevent RRP 75,76 . Community‐based programs may address knowledge gaps through provision of comprehensive information about LARC and contraceptive decision support, providing opportunities to obtain advice from trusted peer educators 69 and health professionals in tandem.…”
Section: Discussionmentioning
confidence: 99%